2013
DOI: 10.1186/1471-2474-14-164
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendon ossification after anterior cruciate ligament reconstruction using bone – patellar tendon – bone autograft

Abstract: BackgroundAmong the various complications described in literature, the patellar tendon ossification is an uncommon occurrence in anterior cruciate ligament (ACL) reconstruction using bone – patellar tendon – bone graft (BPTB). The heterotopic ossification is linked to knee traumatism, intramedullary nailing of the tibia and after partial patellectomy, but only two cases of this event linked to ACL surgery have been reported in literature.Case presentationWe present a case of a 42-year-old Caucasian man affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…However, they did not have an immediate postoperative X-ray to prove their hypothesis. In the present case report, we had postoperative CT scan (5 th day) which showed the loose bone fragments in the joint (Figure 2) which support the hypothesis given by Gianluca Camillieri et al 16 & Erdogan et al 19 gave another hypothesis he believed aggressive rehabilitation causes microtrauma within patellar tendon. 19 However same rehabilitation protocol was followed by others patients and none of them showed patellar tendon ossification.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, they did not have an immediate postoperative X-ray to prove their hypothesis. In the present case report, we had postoperative CT scan (5 th day) which showed the loose bone fragments in the joint (Figure 2) which support the hypothesis given by Gianluca Camillieri et al 16 & Erdogan et al 19 gave another hypothesis he believed aggressive rehabilitation causes microtrauma within patellar tendon. 19 However same rehabilitation protocol was followed by others patients and none of them showed patellar tendon ossification.…”
Section: Discussionsupporting
confidence: 87%
“…The cause of patellar tendon ossification is not cleared. Gianluca Camillieri et al 16 gave hypothesis that persistence of bone debris inside the patellar tendon may trigger calcification. However, they did not have an immediate postoperative X-ray to prove their hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ω-3 mice showed lower levels of heterotopic ossification, which is associated with surgical trauma during DMM. Tendon mineralisation has been reported in patients with tendon rupture, and could be a cause of chronic pain 30. Studies have indicated that PGE 2 , a lipid derivative from ω-6 PUFAs, enhances osteogenesis of tendon stem cells, providing a potential explanation for the greater heterotopic ossification in ω-6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of heterotopic calcification reported in the literature was 1.54%–2.58% and inadvertently scattered bone debris in the operative field was described as the most important cause for it 42. Patellar tendon ossification after ACL reconstruction is an extremely rare complication, and till now only three cases have been reported in literature 434445…”
Section: Discussionmentioning
confidence: 99%